Phytochemical and bioactivity studies of Mangifera pajang Kosterm, Aglaia odoratissima Blume and Acacia albida Delile - Ahmad, Sadikah (2014)
Studies on the phytochemicals and bioactivities were carried out towards three plants species; Mangifera pajang Kosterm, Aglaia odoratissima Blume and Acacia albida Delile. Various classes of chemical constituents have been isolated and identified by spectroscopic method including infrared (IR), mass spectrometry, nuclear magnetic resonance (NMR) and by comparison with reported data. Some of the plant extracts and isolated constituents demonstrated potential activity on antibacterial, antioxidant and cytotoxic screening tests. Chromatographic isolation of the kernel, stem bark and leaves extracts of Mangifera pajang Kosterm from Sabah has led to the isolation of an aromatic ester, methyl gallate (28), mixture of benzaldehyde (64) and benzyl alcohol (65), cycloartane triterpenes identified as mangiferonic acid (10), 3β-hydroxy-cycloart-24-ene-26-oic acid (66) and 3β,23-dihydroxy-cycloart-24-ene-26-oic acid (9), lupane triterpenes;lupeol (59) and lupenone (58), steroids; β-sitosterol (46) and stigmasterol (47), monoterpene; trans-sobrerol (67) and a flavonol glycoside identified as quercitrin (68). However, isolation work towards extracts of Aglaia odoratissima also has led to the isolation of compounds (46), (47) and (59). Chromatographic isolation towards extracts of stem bark of Acacia albida has afforded compounds (47) and (59) from its crude hexane and chloroform extracts. Meanwhile, sucrose (69) was obtained from methanol crude extract. All of the crude extract from Mangifera pajang Kosterm, Aglaia odoratissima Blume and Acacia albida Delile were subjected to cytotoxic screening against various cancer cell lines (MCF-7, HeLa and HT-29). Crude ethyl acetate and methanol extracts from kernel show strong cytotoxic activity towards MCF-7 and HeLa cells with IC50 less than 10 μg/mL while crude petroleum ether, chloroform and ethyl acetate extracts of the stem bark show strong to moderate activity against MCF-7,HeLa and HT-29 cancer cell lines with the IC50 values ranging from 5 to 30 μg/mL. Cytotoxic screening on the isolated compounds revealed high cytotoxic activity by compounds (28) and (66) for MCF-7 cell. Meanwhile, compounds (10), (59), (66) and (68) showed high cytotoxic activity towards HeLa cell, while compounds (10), (28) and (68) were also active towards HT-29 cell. However, only crude ethyl acetate and methanol extracts from kernel shows inhibition towards microbes in antimicrobial and antifungal assays. For DPPH assays, the kernel crude extracts show highest free radical scavenging activity with IC50 less than 10 μg/mL, while crude ethyl acetate and methanol extracts of leaves show weak activity with IC50 less than 150 μg/mL. Methyl gallate (28) was the only isolated compound which showed high antifungal activity towards MRSA and high radical scavenging activity with IC50 value of 6.24 ± 0.30 μg/mL.